Critical Time Windows for Air Pollution Exposure and Birth Weight in a Multicity Canadian Pregnancy Cohort. Issue 1 (January 2022) - Johnson, Markey; Shin, Hwashin Hyun; Roberts, Eric; Sun, Liu; Fisher, Mandy; Hystad, Perry; Van Donkelaar, Aaron; Martin, Randall V.; Fraser, William D.; Lavigne, Eric; Clark, Nina; Beaulac, Vanessa; et al.
Abstract : Background: Maternal prenatal exposure to air pollution has been associated with adverse birth outcomes. However, previous studies focused on a priori time intervals such as trimesters reported inconsistent associations. Objectives: We investigated time-varying vulnerability of birth weight to fine particulate matter (PM2.5 ) and nitrogen dioxide (NO2 ) using flexible time intervals. Methods: We analyzed 1, 300 live, full-term births from Maternal–Infant Research on Environmental Chemicals, a Canadian prospective pregnancy cohort spanning 10 cities (2008–2011). Daily PM2.5 and NO2 concentrations were estimated from ground-level monitoring, satellite models, and land-use regression, and assigned to participants from pre-pregnancy through delivery. We developed a flexible two-stage modeling method—using a Bayesian Metropolis–Hastings algorithm and empirical density threshold—to identify time-dependent vulnerability to air pollution without specifying exposure periods a priori . This approach identified critical windows with varying lengths (2–363 days) and critical windows that fell within, or straddled, predetermined time periods (i.e., trimesters). We adjusted the models for detailed infant and maternal covariates. Results: Critical windows associated with reduced birth weight were identified during mid- to late-pregnancy for both PM2.5 and NO2 : –6 g (95% credible interval: –11, –1 g) and –5 g (–10, –0.1 g) per µg/m 3 PM2.5 during gestational days 91–139 and 249–272, respectively; and –3 g (–5, –1 g) per ppb NO2 during days 55–145. Discussion: We used a novel, flexible selection method to identify critical windows when maternal exposures to air pollution were associated with decrements in birth weight. Our results suggest that air pollution impacts on fetal development may not be adequately captured by trimester-based analyses. Abstract : Supplemental Digital Content is available in the text.